Influence of Dietary Supplementation with Complexed Zinc on Meat Quality and Shelf Life of Broilers - Saenmahayak, B.; Singh, M.; Bilgili, S.F.; Hess , J.B. (International Journal of Poultry Science, 2011)
Influence of complexed zinc supplementation on growth performance and meat quality of broiler chickens were assessed at 49 d of age. A total of 960 male broilers were assigned to four dietary treatments: negative control (C), positive control (C + IZn; 40 ppm ZnSO4), C + 40 ppm complexed Zn (C + OZn) and C + IZn + 40 ppm complexed Zn added to the positive control (C + IZn + OZn). Each treatment feed was provided in a three-stage feeding program. No differences (p>0.05) were observed in the body weight, feed conversion, carcass and component yields due to any of the dietary treatments. However, drip loss was significantly (p0.05) but after 28 d of storage, fillets from birds with high levels of zinc showed increased (p0.05) due to any of the dietary treatments.